2005
DOI: 10.1021/cm047874v
|View full text |Cite
|
Sign up to set email alerts
|

Shape and Phase Control of Colloidal ZnSe Nanocrystals

Abstract: Shape-and phase-controlled ZnSe nanocrystals are synthesized in hot mixtures of long-chain alkylamines and alkylphosphines. The variation in the rate of precursor addition, down to low and controlled levels, allows the nucleation, as well as the growth of the nanocrystals, to switch between the wurtzite and the zinc blend structures. Such a level of control leads to a variety of shapes, from spheres to rods to threedimensional structures formed by rod sections interconnected through branching points. The tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
240
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(256 citation statements)
references
References 105 publications
12
240
1
3
Order By: Relevance
“…19 Aspect ratio is sensitive to phosphonic acid alkyl chain length; the shorter the chain, the more elongated and branched are the nanorods. 18,20 Aspect ratio control has been studied for ZnS, ZnSe,16,21 ABSTRACT We demonstrate molecular control of nanoscale composition, alloying, and morphology …”
mentioning
confidence: 98%
“…19 Aspect ratio is sensitive to phosphonic acid alkyl chain length; the shorter the chain, the more elongated and branched are the nanorods. 18,20 Aspect ratio control has been studied for ZnS, ZnSe,16,21 ABSTRACT We demonstrate molecular control of nanoscale composition, alloying, and morphology …”
mentioning
confidence: 98%
“…We propose that the formation of the EuSe NCs requires the amine to act as a reducing agent. [25][26][27][28][29][30][31][32] Our approach is simple and effective, using EuCl 3 (H 2 O) 6 and elemental selenium as Eu and Se sources, respectively. The overall synthetic procedure for EuSe NCs is depicted in Scheme 1.…”
mentioning
confidence: 99%
“…There is a limited body of literature on the preparation of colloidal nanocrystals (NCs) by a reduction route, [25][26][27][28][29] even when amines were used. [30][31][32] It was reported that OLA could reduce Ag + and Au 3+ ions to form Ag and Au nanoparticles, respectively. [33][34][35] Note that for our EuSe NCs prepared in the absence of OLA, we observed the characteristic luminescence of Eu 3+ peaking at 592 nm and 615 nm (Supporting Information Figure S5a).…”
mentioning
confidence: 99%
“…6 More recently, Cozzoli et al studied the shape and phase control of colloidal ZnSe NPs, where the as-prepared NPs exhibited distinguishable, shape-dependent optical properties in the UVblue region. 7 They observed that a red-shift of the bandgap in longer nanorods, or in general branched nanostructures with long rod sections, was generally accompanied by a significant decrease in the photoluminescence (PL) QY, which could be much lower than 1% for the branched structures.…”
mentioning
confidence: 99%